2023
DOI: 10.1111/eci.14067
|View full text |Cite
|
Sign up to set email alerts
|

Association between the use of lipid‐lowering drugs and the risk of inflammatory bowel disease

Abstract: BackgroundObservational studies have suggested an association between lipid‐lowering drugs and inflammatory bowel disease (IBD) risk. This study aimed to assess the causal influence of lipid‐lowering agents on IBD risk using Mendelian randomization analysis.MethodIn a population of 173,082 individuals of European ancestry, 55 single‐nucleotide polymorphisms were identified as instrumental variables for 6 lipid‐lowering drug targets (HMGCR, NPC1LC, PCSK9, LDLR, CETP and APOB). Summary statistics for the genome‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Recently, two MR studies have conducted analyses on the impact of lipid-lowering medications on IBD. In one study, it was found that inhibition of the lipid-lowering drug target NPC1L1 gene expression may increase the risk of developing IBD, which aligns with our research findings [ 47 ]. Another study, utilizing drug-targeted MR analysis, indicated an association between the expression of PCSK9 and an elevated risk of IBD, CD, and UC [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…Recently, two MR studies have conducted analyses on the impact of lipid-lowering medications on IBD. In one study, it was found that inhibition of the lipid-lowering drug target NPC1L1 gene expression may increase the risk of developing IBD, which aligns with our research findings [ 47 ]. Another study, utilizing drug-targeted MR analysis, indicated an association between the expression of PCSK9 and an elevated risk of IBD, CD, and UC [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…Recently, several repurposing studies have evaluated lipid-lowering medications for inflammatory bowel disease treatment. Specifically, genetic variants linked to key lipid drug targets like PCSK9, 57 74 HMGCR, 74 CETP 57 and NPC1L1 75 served as instruments within an MR framework to probe effects on inflammatory bowel disease. PCSK9 57 74 and NPC1L1 75 inhibition is associated with increased inflammatory bowel disease risk, HMGCR inhibition may confer Crohn's disease risk, while CETP inhibition lowers the risk of Crohn's disease.…”
Section: Drug Target Explorationmentioning
confidence: 99%
“…Specifically, genetic variants linked to key lipid drug targets like PCSK9, 57 74 HMGCR, 74 CETP 57 and NPC1L1 75 served as instruments within an MR framework to probe effects on inflammatory bowel disease. PCSK9 57 74 and NPC1L1 75 inhibition is associated with increased inflammatory bowel disease risk, HMGCR inhibition may confer Crohn's disease risk, while CETP inhibition lowers the risk of Crohn's disease. 57 74 In addition, the association between genetically proxied longterm ACE inhibition and the risk of colorectal cancer has been explored.…”
Section: Drug Target Explorationmentioning
confidence: 99%